(منشطات نمو للنباتات (صديقة للبيئة - صالح خالد مصطفى; عباس هوازن عبدلله; حواس حسين جبار (Al-Nahrain Journal of Science, 2013)
Been working in this research on the use of natural materials and plant extracts, namely, (brewer’s yeast) and (extract licorice) where these materials used are environmentally friendly without any damage caused to humans or the environment, these natural materials are applied on different plants such as tomatoes and wheat and cowpea and ornamental plants such as plant Gazania SPLENDENS and some oil crops such as sunflower. The results show the process as the percentage increase in length for tomato plant which was about (107) cm and weight of the crop was about (1.165) kg of tomato treatment textured spray. Compared with tomato untreated textured spray with an increase in length (82) cm and crop yield (273) g. And plant wheat the increase in length (79) cm compared with the wheat untreated material reaching (60) cm and weight of the crop of wheat treatment textured spray was (45) g and untreated material about (31) g, and plant cowpea The increase in length of about (29) cm to lobby treatment textured spray compared with cowpea untreated material was increase in length (10) cm and weight of the crop of peas treatment was (3.57) g and untreated was (zero). The increase in length of the plant Gazania SPLENDENS treatment textured spray around (23) cm and Gazania SPLENDENS untreated material (18) cm, either sunflower treatment textured spray amounted increase in length (154) cm compared with sunflower untreated material about (75) cm and this shows that the materials used were doping substances of various plants has brought efficiency in the early vegetative growth and the speed growth, and also increase the quantity of production.